Penanganan Limbah Rumah Tangga dan Sampah pada Masyarakat Perspektif Ekologi Islam - Fatrilia Rasyi Radita (Fakultas Dakwah IAIN Jember, 2021)
The waste problem is a major problem faced by almost all big cities in Indonesia. This is inseparable from the problem of urban development related to population, social, and economical aspects which has a very broad impact on human health. Whereas Islam teaches mankind to always preserve the environment and invites humans to live side by side in harmony with the natural surroundings. There are many arguments from the Qur'an and hadith that explain the preservation of the environment and the prohibition of damaging the existence of the surrounding environment. The current study is a library research. The research process was carried out by employing literature studies to collect relevant data from literature, books, and the Internet. Afterwards, the results of the study is presented in description. The way the household waste was handled in the society was in accordance with the waste management system which begins with waste collecting, followed with waste storing and waste transporting. By emphasizing how Islam teaches all Muslim to show compassion in everything including fellow humans, nature, animals and their surrounding, as well as to remind them that damage can occur from the hands of humans themselves, therefore, it is proper for a pious Muslim to always hold fast to his faith by preventing such damage by caring for the surrounding environment.